Effect of soy flour substitution and coconut sugar concentration on protein content and glycemic index of Sihobuk peanut biscuits - Wahyu Haryati Maser; Efrillin Natasya Panggabean; Ajuan Ritonga; Muhamad Hasdar; Damian Laryea (IOP Conference Series Earth and Environmental Science, 2026)
Abstract This study aimed to investigate the effects of soy flour substitution for wheat flour and coconut sugar concentration on the protein content and glycemic index of Sihobuk peanut biscuits. A factorial Completely Randomized Design (CRD) was used involving with two factors: the ratio of soy flour to wheat flour (T1 = 70%:30%, T2 = 75%:25%, T3 = 80%:20%, and T4 = 85%:15%) and coconut sugar concentration (G1 = 15%, G2 = 25%, G3 = 35%, and G4 = 45%). The analyzed parameters were protein content (%) and glycemic index. The results showed that both soy flour substitution and coconut sugar concentration significantly affected protein content (P<0.01). The glycemic index value of Sihobuk peanut biscuits was 41.27, indicating a low glycemic response. These findings suggest that incorporating soy flour and coconut sugar can improve the nutritional quality of traditional Sihobuk peanut biscuits, making them a potential functional food with enhanced protein content and a low glycemic index. By utilizing locally sourced ingredients and improving the nutritional profile of traditional foods, this approach supports food security and promotes sustainable food production aligned with global development goals.
Keywords: Food composition and properties; Coconut Research and Applications; Peanut Plant Research Studies